The Competitiveness of Global Port-Cities: The Case of the Seine Axis (Le Havre, Rouen, Paris, Caen), France - Merk, Olaf (OECD Regional Development Working Papers, 2011)
This working paper offers an evaluation of the performance of the ports of the Seine Axis (Le Havre, Rouen, Caen and Paris), as well as an analysis of the impact of the ports on their territory and an assessment of policies and governance in this field. It examines declining port performance in the last decade and identifies the principal factors that have contributed to it. In addition, the report studies the potential for synergies between the different ports, and surveys impending developments that are likely to influence port performance. The effect of the ports on economic, social and environmental questions is studied and quantified where possible. The value added of the port cluster of Le Havre/Rouen is calculated and its interlinkages with other economic sectors and other regions in France delineated. The paper outlines the impact of the ports' operations, and shows how their activities spill over into other regions. The major policies governing the ports are assessed, along with policies governing transport and economic development, innovation, the environment and spatial planning. These include measures instituted by the port authorities, as well as by local, regional and national governments. Governance mechanisms at these different levels are described and analysed. A port reform package, implemented in 2011, has changed the roles of the principal actors within the ports, and initiatives at the regional level have been intensified. Based on the report's findings, recommendations are proposed with a view to improving port performance and increasing the positive effects of the ports on their territory